After-school poly-strengths programming for urban teens at high risk for violence exposure. Issue 3 (16th May 2019) - Cromer, Kelly D; D'Agostino, Emily M; Hansen, Eric; Alfonso, Caitlin; Frazier, Stacy L
Abstract: Violence exposure increases teens' risk for emotion dysregulation, anxiety, depression, and aggression towards peers. Teens of color are disproportionately more likely to be exposed to violence and less likely to receive mental health services. Community after-school programs can help reduce disparities by offering opportunities for skills development and mental health promotion to mitigate risk associated with violence exposure. The present study explores the promise of a parks-based after-school paid internship program for black and Latinx teens with weekly, group-based enrichment to promote educational attainment, job skills, and health behaviors. University and park administrators collaborated to design a program comprised of paid work (10 hr/week at US$9.05/hr) and weekly 2 hr enrichment (e.g., job skills, meditation, and sleep health psychoeducation). The sample includes 38 youth ( n = 38; 15–17 years old [ M = 16.26, SD = .73]; 42.1 per cent female; 95.2 per cent non-Latinx black, 4.8 per cent Latinx white). Data analyses include pre-/post-measures of violent and nonviolent adversity, emotion regulation, anxiety, depression, and self-efficacy to manage peer conflict. There were no significant changes from Time 1 (T1) to Time 2 (T2) in teen-reported cognitive reappraisal, emotion suppression, anxiety, depression, or self-efficacy to resolve peer conflict. Teens with more violence exposure at T1 reported significant reductions in anxiety at T2. Teens with more overall adversity reported significant reductions in anxiety and improvements in self-efficacy to resolve peer conflict. Findings indicate that after-school programs infused with poly-strengths programming can benefit diverse teens at high risk for violence exposure. Abstract : Black and Latinx teens who participated in parks-based after-school enrichment activities including meditation reported less anxiety and better ability to manage peer conflict without violence.